Upaya Meningkatkan Aktivitas dan Hasil Belajar Bahasa Indonesia Materi Teks Cerita Ulang dengan Teknik Uji Kemahiran Bahasa Indonesia (UKBI) bagi Siswa Kelas XI TIPTL 1 SMK Negeri 2 Kebumen Tahun Pelajaran 2015/2016 - Nurhayati, Siti Samsinar (LP3 Universitas Negeri Semarang, 2016)
The class activity research aims to increase the activity of the students in the learning process as well as Bahasa learning results content story telling text in particularly the basic competence understand the structure and rules story and basic competence rewrite in a nutshell/abstraction the story with Indonesia Language Proficiency Test Engineering (UKBI) in class XI TIPTL 1 2 Kebumen Vocational High School in school tree meetings. The basic competency of first cycle is understanding the structure and rules of the text of the story. The basic competency of second cycles rewrite in a nutshell/abstraction text stories. The results of this research proves that the use of The Bahasa Proficiency techniques to increase activity and learning outcomes grade XI TIPTL 1.